1998
DOI: 10.1021/jf980714h
|View full text |Cite
|
Sign up to set email alerts
|

Bay Laurel Contains Antimutagenic Kaempferyl Coumarate Acting against the Dietary Carcinogen 3-Amino-1-methyl-5H-pyrido[4,3-b]indole (Trp-P-2)

Abstract: A novel antimutagen in bay laurel (Laurus nobilis L.) acts against the dietary carcinogen 3-amino-1-methyl-5H-pyrido[4,3-b]indole (Trp-P-2). The antimutagen was purified chromatographically from ethyl acetate extract of bay leaf and identified instrumentally to be 3-kaempferyl p-coumarate. The yield was 20 mg from 100 g of bay, and its IC50 value, the amount required for 50% inhibition of the mutagenicity of 20 ng of Trp-P-2, was 1.9 μg. This value is close to those for strong antimutagens such as flavones and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…From the spectra data, it was found that the structure of the compound belongs to flavonoid group and when the structure was compared with established literature data, it was identified as 3,5,7,4′-tetrahydroxyflavone (kaempferol). [ 19 20 ]…”
Section: Resultsmentioning
confidence: 99%
“…From the spectra data, it was found that the structure of the compound belongs to flavonoid group and when the structure was compared with established literature data, it was identified as 3,5,7,4′-tetrahydroxyflavone (kaempferol). [ 19 20 ]…”
Section: Resultsmentioning
confidence: 99%
“…The anticancer activities of these extracts have driven the bioactivity-guided isolation of the responsible active compounds. Thus, lauroside B (76), a megastigmane glycoside from a methanolic extract of laurel leaves [211]; kaempferol-3-O-pcoumarate (134), a flavonoid from an ethyl acetate extract of laurel leaves [85]; costunolide (16), santamarine (28), reynosin (31), 11,13-dehydrosantonin (42), gazaniolide (45), spirafolide (48), and lauroxepine (65), sesquiterpenoids from a methanolic extract of laurel fruits [39]; anhydroperoxycostunolide (21) and 3-oxoeudesma-1,4(15),11(13)triene-12,6α-olide (43), sesquiterpenoids from a hot water extract of laurel leaves [94]; dehydrocostus lactone (22) and 3-chlorodehydrocostus lactone (25), sesquiterpenoids from a petroleum ether extract of laurel leaves [50]; costunolide (16), dehydrocostus lactone (22), 3-chlorodehydrocostus lactone (25), and lactone 49, sesquiterpenoids from a chloroform extract of laurel leaves [50,207]; lucentolide (20), anhydroperoxycostunolide (21), santamarine (28), reynosin (31), hydroperoxide-magnolialide (32), magnolialide (35), 3-peroxyarmefolin (36), 11,13dehydrosantonin (42), tubiferin (44), some more eudesmane lactones (30, 33, 34, 37, 38, 47), and several -hydroxyesters (60-64), all sesquiterpenoids from a dichloromethane extract of laurel leaves [52], have been isolated as the active compounds.…”
Section: Review On Laurus Nobilismentioning
confidence: 99%
“…In design E, TA98 cells wereˆrst mutated by incubation with Trp-P-2 and S9, and then incubated with the products, as an assay to detect bio-antimutagenicity. 38) Compared to design A, 13-MLOOH showed similar suppression in designs C and D, suggesting that it aŠected S9 and the activated Trp-P-2. PLPCOOH and C3 were more suppressive in design D, indicating that they acted on the activated Trp-P-2.…”
Section: Resultsmentioning
confidence: 88%